Utilizing Biochar Potential in Nganjuk Regency: Reducing Climate Change Effects and Enhancing Rural-Urban Linkage through Low Carbon Green Growth Program (Lesson Learned from Kameoka City, Japan) - Eko Wahyudi (Department of Urban and Regional Planning, Universitas Diponegoro, 2018)
Climate change is a global issue that all governments have to encounter nowadays. In recent years, many governments are aware of the environmental issues necessary to agenda setting in their development objectives. Sustainable Development Goals (SDGs) conducted by the United Nations gives guidelines for the governments to integrate both economic and environmental issues in a sustainable development framework. Meanwhile, the rural development has also become a global agenda in reducing the disparity between urban and rural areas. Many governments have conducted development strategies for ensuring economic prosperity along with ecological sustainability, yet for generating rural-urban equality as well. Low Carbon Green Growth Program is one of the strategies aimed to meet those objectives. The main purpose of the program is to reduce carbon dioxide emission to minimize the effects of greenhouse gasses (GHGs) as the main cause of climate change and global warming. An immediate action useful to implement the program is managing and utilizing biochar in agricultural process. Previous studies have proved that the biochar reduces CO2 emission and also restores soil fertility. One of the best applicable Low Carbon Green Growth Programs might be the pilot project conducted in Kameoka City of Japan called The Carbon Minus Project. The project’s main purpose is to reduce carbon emission by promoting a low-carbon lifestyle, yet economically profitable. Nganjuk Regency generates abundant biomass from agriculture products, livestock, plantation, and forestry. The solid biomass can be converted into biochar through a pyrolysis process. The result of this study is expected to be taken into consideration by the local governments to promote low carbon lifestyle, to combat climate change, and yet to reduce the rural-urban disparity.